2016
DOI: 10.1523/jneurosci.2768-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Neuropathic Pain: It's about the Rhythm

Abstract: The neural mechanisms underlying the development and maintenance of chronic neuropathic pain remain unclear. Evidence from human investigations suggests that neuropathic pain is associated with altered thalamic burst firing and thalamocortical dysrhythmia. Additionally, experimental animal investigations show that neuropathic pain is associated with altered infra-slow (Ͻ0.1 Hz) frequency oscillations within the dorsal horn and somatosensory thalamus. The aim of this investigation was to determine whether, in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 62 publications
5
104
0
2
Order By: Relevance
“…This scenario is thought to lead to hyper-excitability, sensitization, and enhanced bursting of thalamic neurons. Imaging and biochemical studies in humans further support the notion that TRN neurons are inhibited during chronic pain (Henderson et al, 2013; Gustin et al, 2014; Alshelh et al, 2016; Henderson and Di Pietro, 2016). However, there is latent contradiction in the assumption that thalamic bursts are increased while TRN activity is simultaneously suppressed.…”
Section: Thalamic Bursts: Epic Pain Response Via Thalamic Reticular Nmentioning
confidence: 72%
“…This scenario is thought to lead to hyper-excitability, sensitization, and enhanced bursting of thalamic neurons. Imaging and biochemical studies in humans further support the notion that TRN neurons are inhibited during chronic pain (Henderson et al, 2013; Gustin et al, 2014; Alshelh et al, 2016; Henderson and Di Pietro, 2016). However, there is latent contradiction in the assumption that thalamic bursts are increased while TRN activity is simultaneously suppressed.…”
Section: Thalamic Bursts: Epic Pain Response Via Thalamic Reticular Nmentioning
confidence: 72%
“…Informed written consent was obtained for all procedures according to the Declaration of Helsinki and the study was approved by our local Institutional Human Research Ethics Committees. A subset of the neuroimaging data (not spectroscopy or EEG data) from 11 of the 20 chronic pain subjects was used in a previous investigation (Alshelh et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…While these previous studies used both electroencephalography and magnetoencephalography techniques to explore resting brain rhythms in individuals with neuropathic pain in different body locations, they consistently found increases in resting low‐frequency cortical power in individuals with neuropathic pain. Similarly, we used resting‐state functional magnetic resonance imaging to demonstrate significantly increased infra‐slow oscillation power (0.03–0.06 Hz) within the ascending pain pathway, including the thalamus, in individuals with chronic orofacial neuropathic pain (Alshelh et al, ). We demonstrated that increased infra‐slow oscillations were temporally coupled across specific regions in the ascending pain pathway, including the ventroposterior medial thalamus, the thalamic reticular nucleus (TRN), and the orofacial representation in the primary somatosensory cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Alshelh et al used resting-state fMRI in orofacial neuropathic pain patients to identify increased infra-slow oscillatory activity in the ascending pain pathway, including the spinal trigeminal nucleus, somatosensory thalamus, thalamic reticular nucleus, and primary somatosensory cortex; this increased oscillatory activity was not seen in control patients without orofacial pain [127]. This rhythm showed increased regional homogeneity in the spinal trigeminal nucleus region, consistent with a local spread of neural activity by astrocytes, and was suggestive of a self-sustaining thalamocortical dysrhythmia.…”
Section: Evidence For Central Mechanisms: Clinicalmentioning
confidence: 99%